Pengaruh Price Earning Ratio (PER), Return On Equity (ROE) Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderasi Pada PT. Unilever Tbk Periode 2015-2022 - Natasha Marvela Soesanto; Sri Wahyuni Mega; Diana Ambarwati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The value of the company is reflected in the share price of the company which is reflected in the bargaining power of the shares. Company growth is one indicator or measurement of how the company is developing or grow in a certain period. This study was conducted to examine the effect of price earning ratio, profitability and company size on company value with capital structure as a moderation variable in PT. Unilever Tbk Period 2015-2022. The sampling technique in this study is using the purposive sampling method. The population in this study was 1 company with a sample of 32 financial statements. This study used quarterly data with a total of 32 samples and used SPSS 25 as a statistical test tool to test descriptive statistical tests. Classical assumption test, hypothesis test, multiple linear regression test and residual test. The results showed that the price earning ratio, profitability and size of the company had a positive effect on the value of the company. Capital structure weakens the relationship between price earning ratio, profitability and company size to company value.